The Effects of Eight Weeks Swimming Training on Interleukin- 17, Interleukin- 18 and Tumor Necrosis Factor-α in Streptozotocin Induced Diabetic Rats - Mahboobe Karbalayi; Mehdi Noura; Mohsen Noura (Islamic Azad University, 2016)
Introduction: Inflammation is a feature of the diabetes disease. The aim this study was to determine the effects of eight weeks swimming training on Interleukin- 17 (IL-17), Interleukin- 18 (IL-18) and tumor necrosis factor- α (TNF-α) in streptozotocin-induced diabetic rats. Methods: In this experimental study, 30 diabetic rats were accidentally divided into two equal groups of 15: swimming training and control. The rats in the swimming training group swam for eight weeks, three sessions per week; in the first two weeks for 10 minutes and six weeks later for 30 minutes. The control group rats had no sports activity. 24 hours after the last training session, the rats were sacrificed to measure the parameters in the study. The data were analyzed using SPSS version 19 and paired sample t-test (p≤0.05). Results: eight weeks of swimming training had no significant effect on reduction of IL-17 (p = 0.30), IL-18 (p = 0.41) and TNF-α (p = 0.81) in diabetic rats. Conclusion: it can be concluded that the present training has no significant effect on inflammatory factors in diabetic rats.